2015
DOI: 10.5433/1679-0359.2015v36n5p3421
|View full text |Cite
|
Sign up to set email alerts
|

Citrus pulp in lamb diets: intake, digestibility, and ruminal parameters

Abstract: This study aimed to evaluate the viability of replacing corn meal with citrus pulp (0, 25, 50, 75, and 100 % dry matter of corn meal) by evaluating several nutritional parameters such as intake and digestibility of nutrients, and ruminal fermentation parameters. The diets were formulated to be isoproteic with a roughage:concentrate ratio of 60:40. Five crossbred lambs with an initial average weight of 26.1 ± 1.8 kg were used and distributed in a 5 x 5 Latin Square design. For digestibility of nutrients was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
2
5
1
2
Order By: Relevance
“…Results of our studies are in agreement with Peixoto et al (2015) who found non-significant differences of various levels of dried citrus pulp on ammonia nitrogen. This ammonia nitrogen is necessary to promote growth of fiber degrading bacteria which use ammonia nitrogen as nitrogen source, resulting in improved fiber digestion.…”
Section: Nitrogen Metabolismsupporting
confidence: 93%
“…Results of our studies are in agreement with Peixoto et al (2015) who found non-significant differences of various levels of dried citrus pulp on ammonia nitrogen. This ammonia nitrogen is necessary to promote growth of fiber degrading bacteria which use ammonia nitrogen as nitrogen source, resulting in improved fiber digestion.…”
Section: Nitrogen Metabolismsupporting
confidence: 93%
“…In our study, we incubated CBP and MT as energy and nitrogen sources in supplemented media with inorganic nitrogen and organic nitrogen sources. A recent study by Peixoto et al (18) reported higher values for CP (6.0), NDF (18.3), and ADF (13.7% DM) in citrus pulp, whereas the OM content of our CBP was higher than that reported by Miron et al (6), 91.2% DM. In earlier research both the NRC (19) and Miron et al (6) found different contents of CP (6.9%, 6.70%), NDF (24%, 21.6%), and ADF (22.2%, 21.2%) in % DM basis.…”
Section: Discussioncontrasting
confidence: 60%
“…In one study, Macias [79] reported an increase in carcass pH up to 45 min postmortem with the dietary inclusion of Ferulic acid from winery by-products in ruminant diets. Several studies have reported that carcass traits were not affected by dietary inclusion of citrus and winery by-products in ruminant diets, except for dressing percentage, which was reduced with the addition of these fruit by-products in ruminant diets [50,[80][81][82][83]. In another trial, Kafantaris [76] observed that an inclusion level of up to 100 g/kg DM of citrus and winery by-products in ruminant diets increased slaughter, warm, and cold carcass weights and longissimus muscle area.…”
Section: Effects On Growth Performance and Carcass Traitsmentioning
confidence: 99%